An Analysis of Risk and Return in the Defense Market: Its Impact on Weapon System Competition - Greer, Willis R.; Liao, Shu S. (Management Science, 1986)
With growing austerity pressures from the Administration, Congress, and the general public, the Government's procurement policy has called for increased use of dual-source competition as a means of reducing acquisition costs. In practice, however, this policy has produced mixed results. The cause seems to be an inadequate understanding of the peculiarities of competition in the Government's market. This paper examines the risk and return available in the defense market, and relates it to the industry's propensity to compete. The results show that intelligent observation of the industry's capacity utilization rate would contribute to the development of a more efficient acquisition policy.